Effect of magnesium ions on the proliferation and osteogenic differentiation of human fetal mesenchymal stem cells - Shreedhar, Priya (2015)
Magnesium alloys have been studied as a candidate material for bone regeneration devices due to their bone-like mechanical properties, enhanced osteoconductivity and the ability to safely degrade in vivo. When Mg alloys degrade in vivo they release Mg2+ ions which in previous studies have been proved to stimulate the proliferation as well as osteogenic differentiation of MSCs, leading to increased bone formation. This study aimed at replicating this in vivo condition by culturing younger and older populations of hfMSCs in various concentrations of MgSO4. This was done in order to find out the optimal concentration of MgSO4 with regards to the proliferation and differentiation of hfMSCs and to determine magnesium’s effect on the diminished proliferative capacity of older populations of hfMSCs. In addition to this, in order to gain a better understanding of the role of magnesium as a regulator of osteogenic differentiation, the hfMSCs were also cultured in altering concentrations of MgSO4. The proliferative capabilities of the hfMSCs were determined through the AlamarBlue® assay. Likewise, in order to understand the osteogenic differentiation abilities of the hfMSCs in response to different MgSO4 concentrations, the Alizarin, Calcium, Von Kossa and Alkaline phosphatase assays were carried out. Through the studies it was made apparent that 8 mM showcased the ability to stimulate the greatest proliferative and osteogenic differentiation response in both young and older populations of hfMSCs. Therefore, it is recommended that Mg based biomaterials should be tested for their release rates of Mg2+ and the ones with a release close to 8mM could be chosen to make bone implants.